Getting Away From it All - National Paint, Varnish (Pamphlets corresponding to radio shows produced by the National Paint, Varnish and Lacquer Association, 1940)
Booklet corresponding to a radio broadcast program created by the National Paint, Varnish, and Lacquer Association. The booklet provides tips for finding a summer home and suggests purchasing a simple, cheap property and sprucing it up with a fresh coat of paint. Asserts that the time spent re-modeling and decorating a less expensive property to one's exact liking will bring greater satisfaction than purchasing a brand-new summer home. Includes small stylized illustrations throughout and decorated covers. The National Paint, Oil and Varnish Association, Inc., formed in 1933, was the national professional association representing all branches of the paint, oil, and varnish industries.
Keywords: Shellac; Paint materials; Linseed oil; Oilseeds; Varnish and varnishing; Varnish industry; Paint industry and trade; Advertising--Paint; Interior decoration